Manajemen Sumber Daya Manusia di Dinas Perikanan Kabupaten Gorontalo - Ridwan R. Puluhulawa; Rusly Abdurrahaman Idji; Robin Pakudu; Nuzlan Botutihe (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This study aims to obtain an overview of Human Resource Management (HRM) practices at the Fisheries Service of Gorontalo Regency. A descriptive qualitative approach was used in this study, with data collection techniques through interviews, observations, and documentation. The results of the study indicate that planning is carried out through a recruitment process that includes identifying needs, preparing job descriptions, and the orientation process for new employees. In terms of organization, service digitalization is applied to accelerate administration, increasing HR capacity through training, and involving the community in fisheries policies, which have been proven to increase service efficiency by up to 80%. However, implementation has not been optimal due to limited time, resources, communication constraints, and budget constraints. Work supervision involves leaders, supervisory positions, and other relevant parties, with leaders playing a central role in ensuring employee performance. Motivation is provided by providing opportunities for skill development and rewards for performance. Performance evaluations are carried out periodically to measure the achievement of organizational targets and goals. These findings provide important insights into efforts to improve the quality of human resource management in the public service sector.